2016
DOI: 10.1007/s00535-016-1182-4
|View full text |Cite
|
Sign up to set email alerts
|

Fecal calprotectin: its scope and utility in the management of inflammatory bowel disease

Abstract: Gastrointestinal symptoms such as abdominal pain, dyspepsia, and diarrhea are relatively nonspecific and a common cause for seeking medical attention. To date, it is challenging for physicians to differentiate between functional and organic gastrointestinal conditions and it involves the use of serological and endoscopic techniques. Therefore, a simple, noninvasive, inexpensive, and effective test would be of utmost importance in clinical practice. Fecal calprotectin (FC) is considered to be a reliable biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 133 publications
3
47
0
1
Order By: Relevance
“…S100A8/A9 is a critical player during inflammatory responses . Previous studies have shown that, in human diseases, S100A8/A9 can be detected in serum, aspirates or faeces of patients with rheumatoid arthritis , acute rejection , inflammatory bowel disease , lung disease , systemic sclerosis and atherosclerosis . In the context of renal fibrosis, we are the first to show that S100A8/A9 expression is increased in patients with obstructive nephropathy and localizes uniquely to interstitial granulocytes and not to other parenchymal cells, such as epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…S100A8/A9 is a critical player during inflammatory responses . Previous studies have shown that, in human diseases, S100A8/A9 can be detected in serum, aspirates or faeces of patients with rheumatoid arthritis , acute rejection , inflammatory bowel disease , lung disease , systemic sclerosis and atherosclerosis . In the context of renal fibrosis, we are the first to show that S100A8/A9 expression is increased in patients with obstructive nephropathy and localizes uniquely to interstitial granulocytes and not to other parenchymal cells, such as epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages of our classification algorithm is that only 4 molecules comprise the panel, and 2 of them are already established in hospitals: CEA is routinely measured for various types of tumours, while CAL is also quantified for its utility in inflammatory colon processes33. This makes our 4-marker panel simple and affordable to guide clinical decision-making and complement CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used blood markers for IBD have been C reactive protein (CRP) and erythrocyte sedimentation rate (ESR) but leukocyte count, albumin, and α1 acid glycoprotein have also been used . Fecal calprotectin was introduced approximately two decades ago as a marker of inflammatory bowel disease, and has over the years been shown to have a higher sensitivity and specificity for IBD than ESR . Fecal calprotectin is mainly released from granulocytes in inflamed areas in the gut .…”
Section: Introductionmentioning
confidence: 99%